Displacement Monitoring during the Excavation and Support of Deep Foundation Pit in Complex Environment - Zhouqiang Li (Advances in Civil Engineering)
Taking a super large deep foundation pit project as an example, the horizontal displacement of crown beam and driveway, surface settlement, axial force of anchor cable, and underground water level in the construction process of the foundation pit are dynamically monitored and analyzed. The excavation deformation rule of the deep foundation pit and the influence of excavation on surrounding buildings are analyzed. The results show that, with the excavation of the foundation pit, the crown beam and driveway of the foundation pit incline towards the direction of the pit and eventually tend to be stable. The variation of axial force of the prestressed anchor cable in the first layer of the foundation pit is basically consistent with the variation of horizontal displacement time history. The variation trend of the groundwater level at each side of the foundation pit is different but tends to be stable in a short time. In the whole monitoring period, the cumulative settlement value of each area of the foundation pit is within the controllable range, but the surface settlement of the north side of the foundation pit and a surrounding building has not reached stability, so it is suggested to extend the monitoring time of settlement in the relevant area.